Crystal clear: the autobiographies of Sir Lawrence and Lady Bragg - Bragg, Lawrence (Oxford University Press, 2015)
The main body of this book contains the hitherto unpublished autobiographies of both William Lawrence Bragg, an innovative scientist who won the Nobel Prize for Physics in 1915, and his wife, Alice, a Mayor of Cambridge and National Chairman of Marriage Guidance. Their autobiographies give unusual insights into the lives and times of two distinguished people and the real personalities behind their public appearance.